Human ALPI deficiency causes inflammatory bowel disease and highlights a key mechanism of gut homeostasis. Issue 4 (22nd March 2018) - Parlato, Marianna; Charbit‐Henrion, Fabienne; Pan, Jie; Romano, Claudio; Duclaux‐Loras, Rémi; Le Du, Marie‐Helene; Warner, Neil; Francalanci, Paola; Bruneau, Julie; Bras, Marc; Zarhrate, Mohammed; Bègue, Bernadette; et al.
Abstract: Herein, we report the first identification of biallelic‐inherited mutations in ALPI as a Mendelian cause of inflammatory bowel disease in two unrelated patients. ALPI encodes for intestinal phosphatase alkaline, a brush border metalloenzyme that hydrolyses phosphate from the lipid A moiety of lipopolysaccharides and thereby drastically reduces Toll‐like receptor 4 agonist activity. Prediction tools and structural modelling indicate that all mutations affect critical residues or inter‐subunit interactions, and heterologous expression in HEK293T cells demonstrated that all ALPI mutations were loss of function. ALPI mutations impaired either stability or catalytic activity of ALPI and rendered it unable to detoxify lipopolysaccharide‐dependent signalling. Furthermore, ALPI expression was reduced in patients' biopsies, and ALPI activity was undetectable in ALPI‐deficient patient's stool. Our findings highlight the crucial role of ALPI in regulating host–microbiota interactions and restraining host inflammatory responses. These results indicate that ALPI mutations should be included in screening for monogenic causes of inflammatory bowel diseases and lay the groundwork for ALPI‐based treatments in intestinal inflammatory disorders. Synopsis: Whole‐exome sequencing in two unrelated patients with severe intestinal inflammation identified loss‐of‐function mutations in ALPI, a brush border enzyme which detoxifies lipopolysaccharides (LPS) through dephosphorylation of its lipid A moiety, linking ALPI deficiency to inflammatory bowel diseases. Structural modelling of ALPI mutants indicated that affected residues are critical for inter‐subunit interactions. Heterologous expression of ALPI mutants in HEK293T cells demonstrated that all mutations were loss of function and impaired either stability or catalytic activity of ALPI which could no more detoxify LPS. ALPI expression was strongly decreased in small intestinal biopsies from ALPI deficient patients. ALPI activity was undetectable in ALPI deficiency patient's stools. Abstract : Whole‐exome sequencing in two unrelated patients with severe intestinal inflammation identified loss‐of‐function mutations in ALPI, a brush border enzyme which detoxifies lipopolysaccharides (LPS) through dephosphorylation of its lipid A moiety, linking ALPI deficiency to inflammatory bowel diseases.